Effects of glycogen synthase kinase-3β activity inhibition on cognitive, behavioral, and hippocampal ultrastructural deficits in adulthood associated with adolescent methamphetamine exposure - Yan, Peng; Liu, Jincen; Ma, Haotian; Feng, Yue; Cui, Jingjing; Bai, Yuying; Huang, Xin; Zhu, Yongsheng; Wei, Shuguang; Lai, Jianghua (Frontiers in Molecular Neuroscience, 2023)
Objective Glycogen synthase kinase-3β (GSK3β) has been implicated in the maintenance of synaptic plasticity, memory process, and psychostimulant-induced behavioral effects. Hyperactive GSK3β in the Cornu Ammonis 1 (CA1) subregion of the dorsal hippocampus (DHP) was associated with adolescent methamphetamine (METH) exposure-induced behavioral and cognitive deficits in adulthood. This study aimed to evaluate the possible therapeutic effects of GSK3β inhibition in adulthood on adolescent METH exposure-induced long-term neurobiological deficits. Methods Adolescent male mice were treated with METH from postnatal day (PND) 45–51. In adulthood, three intervention protocols (acute lithium chloride systemic administration, chronic lithium chloride systemic administration, and chronic SB216763 administration within CA1) were used for GSK3β activity inhibition. The effect of GSK3β intervention on cognition, behavior, and GSK3β activity and synaptic ultrastructure in the DHP CA1 subregion were detected in adulthood. Results In adulthood, all three interventions reduced adolescent METH exposure-induced hyperactivity (PND97), while only chronic systemic and chronic within CA1 administration ameliorated the induced impairments in spatial (PND99), social (PND101) and object (PND103) recognition memory. In addition, although three interventions reversed the aberrant GSK3β activity in the DHP CA1 subregion (PND104), only chronic systemic and chronic within CA1 administration rescued adolescent METH exposure-induced synaptic ultrastructure changes in the DHP CA1 subregion (PND104) in adulthood. Conclusion Rescuing synaptic ultrastructural abnormalities in the dHIP CA1 subregion by chronic administration of a GSK3β inhibitor may be a suitable therapeutic strategy for the treatment of behavioral and cognitive deficits in adulthood associated with adolescent METH abuse.